Meta-Analysis of Sustainable Urban Drainage Systems (SUDS) in Reducing Urban Flood Risks - Tri Satriawansyah; Muhammad Kasim; Fantoni; Dewanto; M.Rudi Fanani (AKADEMI TEKNIK ADI KARYA, 2024)
Urbanization and climate change have increased the risk of flooding in cities. Sustainable Urban Drainage Systems (SUDS) offer a promising approach to mitigate these risks by managing stormwater runoff. This study aims to conduct a meta-analysis to assess the effectiveness of SUDS in reducing urban flood risks. This research is a type of meta-analysis research. The study investigated the impact of SUDS on flood reduction. Data on different types of SUDS, precipitation events, and flood risk metrics were extracted. Standardized mean differences (SMDs) are calculated to measure the overall impact of SUDS on flood reduction. The meta-analysis revealed a significant positive effect of SUDS on reducing urban flood risks. The effect size varied depending on the type of SUDS and the severity of the rainfall event. Overall, SUDS demonstrated effectiveness in mitigating flood risks associated with various storm intensities with effect size value = 0.801. This meta-analysis provides robust evidence for the effectiveness of SUDS in reducing urban flood risks. The findings support the wider adoption of SUDS as a key strategy for sustainable urban development and flood risk management.